S-Brane Solutions with Accelerating Cosmology in M-theory - Freddy Permana Zen; Arianto Arianto; Bobby Eka Gunara; Selly Feranie (Institut Teknologi Bandung, 2006)
We study the expansion and accelerated expansion of universe from S-branes of the M-theory. The dynamics of expansion is described by the scale factor of S-brane solutions and equation of state from the S-bran dark energy models. We provide analytic expressions to calculate the equation of state of these models as a function of time. Moreover, we also study cosmological expansion with the intersection solutions, which may have an interesting characteristic, namely, they never obtain the accelerated expansion. The critical expansion is given by the limit Î²â0.